ANALYSIS OF THE EFFECT OF MARKETING MIX DECISIONS TO PURCHASE THE PRODUCT HAND PHONE - Setyawan, Aris (Accounting, 2010)
Today cell phones are used more and more people. One of handphone users are students. To determine the influence of the phenomenon of marketing mix variables to the decision to buy Nokia hand phone. The title selected is MARKETING MIX ANALYSIS OF THE EFFECT OF PRODUCT PURCHASE DECISION ON HAND PHONE (Case Study on Hand Phone Users Nokia Students at the College of Economic Sciences Nusa Megarkencana). In accordance with the title of this research, then the problem is formulated as follows: 1) Is the variable- marketing mix variables affect simultaneously and partially on a student's decision School of Economics Nusa Megarkencana in the purchase of Nokia brand mobile phone product? 2) Which marketing mix variables dominant influence on student decision-School of Economics Nusa Megarkencana in the purchase of Nokia brand mobile phone product? The method used to answer the problem formulation was determined by survey method using questionnaire methods of data collection tools. The data obtained was analyzed with linear regression method to research conducted berganda.Dari known that marketing mix variables of product, pricing, distribution, and promotion, influence student decisions simultaneously towards School of Economics in the purchase of Nusa Megarkencana Nokia brand of mobile phone products. Of all the marketing mix variables, individual variables only campaign that has significant influence on purchase decisions on student cell phones Nokia STIE Nusa Megarkendana Yogyakarta. Keywords: Influence, Marketing Mix, Purchase Decision, Hand Phone Product